Project Based Technology Instruction Transforms Educational Personnel Administrative Software Competence: Instruksi Teknologi Berbasis Proyek Mentransformasi Kompetensi Perangkat Lunak Administrasi Tenaga Kependidikan - Muchammad Ubaidillah; Hendra Sukmana; Nuril Ubud Sugistyn; Reina Anali; Setyoning Alanzah; Yusril Lifalillah (Proceedings of The ICECRS, 2025)
General Background Information and communication technology constitutes an integral component of modern administrative operations and public service delivery within educational institutions. Specific Background In Indonesia, education personnel frequently lack fundamental digital proficiencies, including word processing and online communication, due to infrastructure limitations, budget constraints, and insufficient institutional awareness. Knowledge Gap While human capital theory posits that targeted capability building increases organizational productivity, a significant discrepancy remains regarding how practical instructional frameworks address varying technical assimilation rates among non-teaching school staff. Aims This study analyzes a project-based information technology training initiative targeting education personnel at SMA Negeri 1 Gedangan to evaluate its practical outcomes. Results Qualitative descriptive analysis reveals that project-based methodologies significantly advance functional capabilities, particularly in operating Canva and Microsoft Office applications, although individual assimilation rates varied considerably based on personal motivation, background, and learning styles. Novelty This research specifically identifies practical project-based learning as a definitive catalyst for bridging diverse digital skill disparities among non-teaching school administrative staff. Implications Educational organizations must prioritize personalized support, regular capability evaluations, and robust infrastructure investments to sustain long-term operational efficiency and public service quality. Highlights: Hands-on mentoring significantly advances staff capabilities in utilizing digital design and document processing applications. Individual variations in learning styles and personal motivation directly dictate the assimilation rate of new digital skills. Continuous personalized support and regular evaluations remain essential for sustaining long-term institutional service quality. Keywords: Information And Communication Technology, Human Capital Theory, Project Based Learning, Public Service Quality, Digital Skills